Medication-overuse headache—a review of different treatment strategies - Krymchantowski, Abouch; Jevoux, Carla; Krymchantowski, Ana Gabriela; Ramos, Luiza Barbosa; Barbosa, Jackeline S. S.; Silva-Neto, Raimundo Pereira (Frontiers in Pain Research, 2023)
Chronic headache could progress to medication-overuse headache (MOH). MOH usually occur due to consumption of analgesics. MOH is considered as noteworthy personal and societal burdens. Identification of risk of MOH and treatment of MOH patients is integral part of comprehensive management of MOH. Medication overuse is a modifiable risk factor in advancement from episodic to chronic migraine. Over the period, MOH is considered as challenging to treat condition; hence, cause lots of debate. Treatment strategies such detoxification and preventive treatment are the debatable issues. Treatment of MOH is complex and experts in the field have variable views on the most appropriate strategy of MOH treatment. Objective of the review is to give comprehensive synopsis of literature in the management of MOH. Medication withdrawal is foundation for the management of MOH. Setting for treatment either inpatient or outpatient usually preferred considering clinical condition of the patient. Literature suggested abrupt withdrawal with and without preventive medicine. Bridging therapy could be useful to get relief from withdrawal symptoms. Multidisciplinary approach proved beneficial in supporting withdrawal and preventing relapse. Worldwide, termination of overused medications has been observed as treatment strategy, other aspects such as complete or measured withdrawal or preventive medicines with or without withdrawal are even now debatable issues.